2017
DOI: 10.1002/jgt.22146
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of (pan, even hole)‐free graphs

Abstract: A hole is a chordless cycle with at least four vertices. A pan is a graph that consists of a hole and a single vertex with precisely one neighbor on the hole. An even hole is a hole with an even number of vertices. We prove that a (pan, even hole)-free graph can be decomposed by clique cutsets into essentially unit circular-arc graphs. This structure theorem is the basis of our ( )-time certifying algorithm for recognizing (pan, even hole)-free graphs and for our ( 2.5 + )-time algorithm to optimally color the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…This implies that x is complete to one of B C , 1 1 and is mixed on the other; by symmetry, we may assume that x is complete to B 1 and mixed on C 1 . This proves (5). This proves (5).…”
supporting
confidence: 59%
See 4 more Smart Citations
“…This implies that x is complete to one of B C , 1 1 and is mixed on the other; by symmetry, we may assume that x is complete to B 1 and mixed on C 1 . This proves (5). This proves (5).…”
supporting
confidence: 59%
“…It is well known that P 4 -free graphs are perfect [26]. Finally, we remark that Gaspers and Huang [14] showed that every P C ( , ) 6 4 -free graph G satisfies ≤ ⌊ ⌋ χ G ω G ( ) (3/2) ( ) , and Chudnovsky and Sivaraman [6] proved that every P C ( , ) 5 5 -free graph G satisfies ≤ χ G ( ) 2 ω G ( )−1 . In contrast, since there exist graphs of arbitrarily large girth and chromatic number [10], the class of C C ( , ) 4 5 -free graphs is not χ -bounded.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations